(untitled) (Bangladesh Critical Care Journal, 2020)
Background: Enteric fever otherwise called Typhoid fever is a systemic disease caused by Salmonella typhi and Salmonella paratyphi, having reservoir in contaminated water and food. It affects considerable number of populations of the world but regions of South Asia are most commonly affected. Aims and Objective: The objective of this study to find the prevalence of Typhoid fever with respect to age, gender, marital status, occupation, seasonal variation, treatment of drinking domestic water source, and clinical features. Methodology: This is a cross- sectional observational study conducted at Bangladesh Medical College Hospital (BMCH), Dhanmondi, Dhaka from January to December 2019. Those presenting both outpatient departments or admitted to the inpatient units with complains of fever and abdominal pain underwent blood culture for the diagnosis of Typhoid fever. Patients with informed consent and positive blood culture report (including both Salmonella typhi and Salmonella paratyphi) were included in the study. Results: Total 1375 tests were performed, out of which 407 came out to be positive blood culture report (including both Salmonella typhi and Salmonella paratyphi). Out of these tests 31.65% were males and 27.35% were females. Highest occurrence of typhoid fever was observed among males of age group 18 – 45 years and least with patients between age group above 75 years. As for the influence of occupation, male civil servants recorded the highest occurrence in the hospitals while artisans recorded the least. The influence of marital status revealed the highest occurrence in the single males with the married females had the least. In relation to months the prevalence was the highest in the month of July - September (11.42%). Water quality, vaccination and season have great impact on the burden of typhoid fever in population. Fever, diarrhea and abdominal pain are the major symptoms associated with typhoid fever. Conclusion: Socio-demographic factors such as age, gender, marital status, and seasonal variation, treatment of drinking water supply, occupation and presenting complaints influenced the distribution pattern of typhoid fever among the population in BMCH, Dhanmondi, Dhaka. Bangladesh Crit Care J September 2020; 8(2): 86-90